Stable Simultaneous CW 1052, 1071, and 1083 nm Narrow Spectral Width Nd-Based Laser Output Using Precise Gain Control With VBGs - Ching-Nien Chen; Te-yuan Chung; Yu-Hua Hsieh (IEEE Photonics Journal, 2018)
A continuous wave Nd-based laser with simultaneous narrow spectral 1052, 1071, and 1083 nm output was achieved by using temperature-controlled volume Bragg gratings to balance the gain competition between each wavelength and stabilize the laser output. Each output wavelength was characterized thoroughly and showed good stability in both frequency and power.